Innovations for Development Awards 1990 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Dr Reg Preston, a consultant to the Convenio Inter-institucional pare la Produccion Agropecuaria en el Valle del Rio Cauca (CIPAV), Colombia has been granted the IDEA award in the target area of farming The award is given by the Innovations for...